Дослідження електроприводу скребкового транспортера зерноочисного агрегату - Постнікова, Марина Вікторівна; Постникова, Марина Викторовна; Postnikova, Marina (My University, 2019)
UK: Метою дослідження є комплексний аналіз втрат активної потужності в системі «електродвигун – робоча машина». Сумісний розгляд характеристик електродвигуна і робочої машини допомагає вирішити такі важливі для вибору привода питання як достатня потужність двигуна, можливість зрушення з місця, розгін до номінальної швидкості за заданий період часу. Запропонована диференційована система оцінки втрат активної потужності в системі «електродвигун – робоча машина», яка дозволяє вибирати інтервали завантаження потокових ліній очищення зерна з мінімумом втрат активної енергії. RU: Вопросам потерь активной мощности в современных исследованиях уделяется большое внимание. Однако, отдельно рассматриваются как электродвигатели, так и рабочие машины. Целью исследований является комплексный анализ потерь активной мощности в системе “электродвигатель - рабочая машина”. Совместное рассмотрение характеристик электродвигателя и машины помогает решить такие важные для выбора привода вопросы как достаточная мощность двигателя, возможность трогания с места, разгон до номинальной скорости в заданное время и так далее. Предложена дифференцированная система оценки потерь активной мощности в системе “электродвигатель – рабочая машина”, позволяющая выбирать интервалы загрузки поточных линий очистки зерна с минимумом потерь активной энергии. EN: There are significant losses of active power in induction motors and working ma-chines of production lines of the agro-industrial complex today. A lot of attention is paid to researches of active power losses. However, induction motors and working machines are considered separately. The purpose of the research is a comprehensive analysis of active power losses in the system “induction motor - working machine”. Joint consideration of the induction motors’ and the machines’ characteristics helps to solve such important issues for choosing a drive as sufficient engine power, the possibility of starting, acceleration to the nominal speed at a specified time and so on. As known, the system “induction motor - working machine” additional to useful active power consumed to perform the required work on the processing of products, there are losses of active power in the driving motor and the working machine. A differentiated estimating for active power losses in the “induction motor - work machine” system is proposed. It allows to select the grain cleaning production lines loading intervals with active energy losses minimum.The main power losses in the driven electrical equipment are due to the techno-logical machines’ working processes. Being analyzed, one can get the information about the efficiency of electric energy usage in a particular technological unit and determine the general methods of energy saving in the grain processing. Therefore, to synthesize an electrical energy specific cost mathematical model of the grain processing, it is nec-essary to analyze the processes of electrical energy conversion in the driven electrical equipment of grain cleaning production lines, as well as more detailed analysis of ener-gy usage when performing technological operations of grain cleaning.
Исследование электропривода скребкового транспортера зерноочистительного агрегата
The scraper conveyor’s electric drive of grain cleaning unit research
Keywords: енергозбереження; електропривод; економія електроенергії; корисна потужність; втрати потужності; энергосбережение; электропривод; экономия электроэнергии; полезная мощность; потери мощности; energy saving; electric; energy saving; useful power; losses power